COMPUTER-BASED STANDARDIZED TESTING (CBT) SUMMATIVE ASSESSMENT: ONE INSTITUTION EXPERIENCE - Naila Rajiha; Setia Rini (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2023)
One tool for measuring the result of learning is the summative assessment using Computer-Based Standardized Testing (CBT). The assessment process and the issues that arise in holding are fascinating to be discussed. This research was focused on: How the CBT final examination test is being implemented in a school in Pati Regency. This study employs descriptive case studies as one of the methods of qualitative research. Interviews, observation, and documentation are the data collection techniques for this study's primary and secondary sources. The researchers used a triangulation data source and triangulation technique to check the data integrity. The authors draw the following conclusions: Students' learning evaluation processes are through various activity procedures, such as simulating, implementing, overseeing evaluations, processing data, and using evaluation results. Moreover, observing student needs and readiness in all forms is an obligation applied in conducting CBT.